Identification and molecular characterization of Orf virus infection in occupationally exposed women in South America - Peralta, Andrea Veronica; Flores Olivares, Carlos; Verna, Andrea Elizabeth; González Altamiranda, Erika; Odriozola, Ernesto Raul; Madariaga, Carolina; Odeon, Anselmo Carlos; Konig, Guido Alberto; Canton, German Jose (Elsevier, 2023)
Contagious Ecthyma (CE) is a severe exanthematous dermatitis caused by the Orf virus (ORFV) that mainly affects domestic small ruminants such as sheep and goats. It is a worldwide-distributed occupational zoonosis, particularly infecting those in close contact with animals or animal products such as shepherds, farmers and veterinarians, among others. In the present work, we report the first human CE case confirmed in Argentina. A phylogenetic analysis based on four gene sequences of the isolated strain responsible for the disease showed that this isolate grouped with other ORFV sequences that caused reported CE cases in sheep from the same Argentine province. We also sequenced a sample from a Chilean human case reported in 2017, whose phylogenetic analysis showed that it groups together with other Argentine isolates from locations close to the border with Chile.